Legislative Amendments to Saudi General Partnership Companies: A Departure from Established Legal Principles - Alomar, Adnan; Al-Amareen, Emad Mohammad; Almajali, Tawfiq Aref (Faculty of Law, Universitas Brawijaya, 2025)
In 2022, the Saudi legislator enacted significant amendments to the Companies Law, particularly regarding General Partnership Companies (GPCs), as part of the broader strategy to align with Vision 2030. These amendments notably allow legal persons to become partners in GPCs, a sharp departure from the long-standing legal doctrine that restricts partnership membership to natural persons due to the personal nature (intuitus personae) of such entities. This study critically examines whether these legislative changes are compatible with the foundational principles of GPCs, raising key questions about the extent of liability borne by legal persons, the preservation of personal trust among partners, and the implications for company dissolution, bankruptcy, and partner succession. Employing a qualitative and doctrinal legal research approach, the analysis draws on statutory texts, case law, and comparative legal frameworks, particularly from Saudi Arabia and Jordan, to assess the coherence and impact of the new provisions. The research finds that while the reforms introduce flexibility and accommodate modern commercial realities, they challenge core legal principles by allowing entities lacking personal identity to participate in structures fundamentally based on mutual trust and joint liability. The study recommends clarifying the extent of legal persons’ financial responsibility and reinforcing the role of personal consideration in partnership governance, including restrictions on share transfers and clearer rules on succession and partner withdrawal. These adjustments are crucial to preserving the legal integrity of GPCs while adapting them to contemporary economic developments.